Dampak Tagline “Gratis Ongkos Kirim” dan Program Flash Sale pada Marketplace Shoppe untuk Mendorong Impulsive Buying secara Online - Yesi Indian Ariska; Nirta Vera Yustanti; Rahayu Ervina (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this research is to see the impact caused by the "Free Shipping" Tagline and FlashSale Program on the Shoppe Marketplace in order to encourage Impulsive Buying online for housewives in Muara Bangkahulu District, Bengkulu City. The format of research conducted by researchers in this study is quantitative research using an association approach. In this study, the sample used was taken using a purposive sampling technique with a sample of 100 respondents. As for the method of analysis, the researcher used the method of testing validity, reliability testing, and testing the hypothesis and using multiple linear regression analysis. From the results of the data processing, the results showed that the Tagline did not significantly influence the impulsive buying decision, while the Flash Sale Program had a significant effect on the online impulsive buying decision. Meanwhile, the regression test shows that the Tagline variable "free shipping" and Flashsale simultaneously or together can have an impact on impulsive buying for housewives in Muara Bangkahulu District. The coefficient of determination test performed shows a fairly close relationship between Tagline and Flash sale, this can be seen from the R value of 0.5650. From the R-Squared Adj value, it can be seen that the tagline and flash sale variables contributed 30. 60%, this proves that these variables can affect Implusive Buying, while the remaining 69.40% is influenced by other variables not discussed by the researchers in this study.